Teología e interculturalidad - Carrasquila, Jesús (2023)
It is necessary therefore to recover a way of life and experience where the depth that exposes the symbol breaks with the reductionism of the practices of our own civilization. Sometimes it is found in our society scarcity of concepts in relation to various practices of different people and cultures. The reality seems that still overflowing us or is it necessary to design new categories to think that reality changes and challenges. In the case of indigenous we easily highlights some practices that challenge us: the defense of life and territory, the role taken by women in their communities, which redefines the relationship between themselves and the demands for respect for their cultural identity, language and political practice. At this point we should learn much from them. The cross point is not alone in traslating the experiences that each identity, the Christian an Indian, but in fostering experiences that allow or promete shared values that concern all and have to do with life, justice, nature, solidarity, community and the sacred.